2021
DOI: 10.1088/1748-9326/abd971
|View full text |Cite
|
Sign up to set email alerts
|

Permafrost-derived dissolved organic matter composition varies across permafrost end-members in the western Canadian Arctic

Abstract: Organic matter, upon dissolution into the aqueous state as dissolved organic matter (DOM), can undergo mineralization by microbes. There has been increasing effort to characterize DOM released from thawing permafrost because it may perpetuate a permafrost carbon feedback. Permafrost-derived DOM often has a composition that can be highly susceptible to mineralization by microbes, but most studies to date that characterize permafrost-derived DOM have been limited to select regions, and tend to focus on a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 63 publications
2
16
0
Order By: Relevance
“…Our results show that the composition and biodegradability of DOM differs between post-glacial landscape units and that these differences are related to the glacial processes. In agreement with our results, a recent study also found a coupling between permafrost soil formation and DOM character for different permafrost end-member types (tills, diamicton, lacustrine, peat, and Yedoma deposits) (MacDonald et al, 2021). In addition, different soil-forming factors such as ice content, permafrost extent and parent material (epigenetic vs. syngenetic formation) shape the biogeochemical response to permafrost thaw in aquatic systems (Tank et al, 2020).…”
Section: Characteristics Of Dom In Mediasupporting
confidence: 92%
“…Our results show that the composition and biodegradability of DOM differs between post-glacial landscape units and that these differences are related to the glacial processes. In agreement with our results, a recent study also found a coupling between permafrost soil formation and DOM character for different permafrost end-member types (tills, diamicton, lacustrine, peat, and Yedoma deposits) (MacDonald et al, 2021). In addition, different soil-forming factors such as ice content, permafrost extent and parent material (epigenetic vs. syngenetic formation) shape the biogeochemical response to permafrost thaw in aquatic systems (Tank et al, 2020).…”
Section: Characteristics Of Dom In Mediasupporting
confidence: 92%
“…In Sweden (Hodgkins et al., 2016), Russia (Gandois et al., 2019), and the Canadian Arctic (Fouché et al., 2017), waters draining permafrost thaw (i.e., thermokarst) features have shown greater contributions of heteroatom‐containing formulae and/or microbial DOM than waters draining less degraded permafrost landscapes, suggesting the increasing importance of microbial DOM sources with increasing water residence time and flow depth in soils due to thaw. Fundamentally, differences in type and extent of permafrost impact hydrology and DOM chemistry (MacDonald et al., 2021; O'Donnell, Aiken, Swanson, et al., 2016). The six watersheds in this study encompass a continuum of types of surface‐groundwater connectivity.…”
Section: Resultsmentioning
confidence: 99%
“…Through the use of FT‐ICR MS, we saw a large number of the aliphatic compounds present in the undegraded permafrost (t0) but absent in the Kolyma River (t0) (Figure ). Recent studies have noted the relative enrichment of aliphatic assigned formula in yedoma permafrost derived DOM (Drake et al., 2018; MacDonald et al., 2021; Spencer et al., 2015). This aliphatic rich signature (high H/C) is a distinctive characteristic of permafrost‐influenced waters and is not reported in either the mainstem of Arctic rivers or other riverine DOM (Drake et al., 2018; Spencer et al., 2015; Stubbins et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, the fate of permafrost DOM is tied to its composition which is linked to how the permafrost formed as well as past thaw modification, with different permafrost endmembers showing marked DOM compositional variability (MacDonald et al., 2021; Spencer et al., 2015; Ward & Cory, 2016). DOC in streams thawing from yedoma permafrost in the Kolyma Basin is 14 C depleted (∼20,000 14 C yBP old) and exhibits an exceedingly aliphatic (high H/C) dissolved organic matter (DOM) compositional signature (Spencer et al., 2015; Stubbins et al., 2017).…”
Section: Introductionmentioning
confidence: 99%